Implementing The Arabic Language Curriculum for The Purpose of Studying Fiqh and Hadith in The Language Preparation Department at Imam Shafi'i University, Jember - Wicaksono, Triadi; Fitriani, Nisa (IJIE International Journal of Islamic Education, 2023)
Current migration often represents a quest for self-betterment and increased religious commitment, mainly accomplished through Arabic language study. This language emphasis stems from the Quran and Sunnah being in Arabic, constituting the core teachings of Islam. Muslims must grasp the foundational elements of Islam, making proficiency in Arabic essential. Learning the language is not merely a duty but a vital prerequisite for understanding and fulfilling the obligations outlined in the Quran and Sunnah, emphasizing the significance of studying Sharia. In a scholarly exploration of motives for learning Arabic, 86% to 98% of respondents were motivated by a desire to learn Islam and gain knowledge of Islamic civilization. This study seeks to outline the application of the Arabic language curriculum specifically designed for studying Fiqh and Hadith within the Language Preparation Department at Imam Shafi'i University in Jember. This study employed a qualitative approach to comprehend the overall experience of the research subject. It utilized descriptive linguistic expressions within a specific natural context, employing diverse scientific methods. The results show that teaching Arabic for specific purposes is segmented into two stages: beginner and advanced. Each stage involves distinct materials and instructional hours. Likewise, there are differences in credit hours between the standard Arabic language program and the specialized program for specific purposes.